Ocular manifestation of granulomatosis with polyangiitis – a case report - Mesterhazy, Marta; Wierzbowska, Joanna; Różycki, Radosław; Rękas, Marek; Tłustochowicz, Witold (Klinika Oczna / Acta Ophthalmologica Polonica, 2019)
Granulomatosis with polyangiitis (GPA, formerly Wegener’s Granulomatosis) is a rare autoimmune multisystem disease of unknown etiology, which is characterized by granulomatous inflammation, tissue necrosis and vasculitidies of small and medium vessels. It has a predilection for the upper respiratory tract, lungs and kidneys, but can affect any organ. Ocular manifestation occurs in around 50% of patients. Appereance of exophthalmos, nasolacrimal duct obstruction, granulomas of eyelid, scleritis or marginal keratitis should lead to consider GPA. In an article a rare case of a 30-year-old man who developed ocular symptomps seven years after diagnosis of GPA, is presented.